The ETRAMP family member SEP2 is expressed throughout Plasmodium berghei life cycle and is released during sporozoite gliding motility. - Chiara Currà (Public Library of Science (PLoS), 2013)
The early transcribed membrane proteins ETRAMPs belong to a family of small, transmembrane molecules unique to Plasmodium parasite, which share a signal peptide followed by a short lysine-rich stretch, a transmembrane domain and a variable, highly charged C-terminal region. ETRAMPs are usually expressed in a stage-specific manner. In the blood stages they localize to the parasitophorous vacuole membrane and, in described cases, to vesicle-like structures exported to the host erythrocyte cytosol. Two family members of the rodent parasite Plasmodium berghei, uis3 and uis4, localize to secretory organelles of sporozoites and to the parasitophorous membrane vacuole of the liver stages. By the use of specific antibodies and the generation of transgenic lines, we showed that the P. berghei ETRAMP family member SEP2 is abundantly expressed in gametocytes as well as in mosquito and liver stages. In intracellular parasite stages, SEP2 is routed to the parasitophorous vacuole membrane while, in invasive ookinete and sporozoite stages, it localizes to the parasite surface. To date SEP2 is the only ETRAMP protein detected throughout the parasite life cycle. Furthermore, SEP2 is also released during gliding motility of salivary gland sporozoites. A limited number of proteins are known to be involved in this key function and the best characterized, the CSP and TRAP, are both promising transmission-blocking candidates. Our results suggest that ETRAMP members may be viewed as new potential candidates for malaria control.